The Influence of Islamic Work Ethics and Transformational Leadership on Organizational Citizenship Behavior (OCB) of Islamic School Teachers in Bandar Lampung - Saringatun Nafingah; Nova Mardiana (Journal of Innovative and Creativity, 2025)
Globalization has created a dynamic environment, requiring organizations in various sectors, including educational institutions to adapt in order to survive and thrive. Islamic schools as educational institutions based on religious values, face challenges in managing human resources. The success of education is not only determined by academic quality, but also by the behavior of teachers in carrying out their duties. Islamic work ethics play an important role in shaping teacher behavioral standards, while transformational leadership has a strategic role in motivating and directing teachers to contribute more than just their main duties. This study aims to analyze the influence of Islamic work ethics and transformational leadership on Organizational Citizenship Behavior (OCB) of Islamic school teachers in Bandar Lampung. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 107 teachers from five Islamic schools in Bandar Lampung. The data analysis technique used simple linear regression with the help of IBM SPSS version 24. The results of the study indicate that this study supports the proposed hypothesis, namely that Islamic work ethics have a positive and significant effect on OCB, and transformational leadership also has a positive and significant effect on OCB. Suggestions for Islamic schools in Bandar Lampung to pay more attention to the implementation of Islamic work ethics values, improve interaction and communication between principals and teachers, and increase teacher awareness and motivation to actively contribute in supporting the principal's duties, so as to encourage an increase in teacher OCB and the quality of education in Islamic schools.